A Closer Look on Disjunctive Coordination: The So-Called Non-Constituent Disjunctive Coordination - Matlotlisang Mokapane Lemohang Tjabaka (REiLA, 2021)
English disjunctive coordination is a clause complex that has two co-ordinands. Many scholars and researchers dealt with this phenomenon using different standard theories. However, there is still a controversy in literature whether non-constituent coordination exists or not; therefore, this research determines whether the disjunctive coordination constituents are non-constituents. The paper also describes the relationship between the disjunctive co-ordinands, coordinated phrases, or clauses joined by conjunction /or/. The article further aims to describe the structure of the disjunctive coordination and the category label of the disjunctive coordinator. The Systemic Functional Grammar and Minimalist Program framed this study. This qualitative paper purposively and conveniently selected from Facebook and WhatsApp groups for the National University of Lesotho's students; 13 structures were chosen from the WhatsApp group, while 15 were taken from Facebook. Results reveal that the disjunctive coordination constituents are not non-constituents. What seems prevailing or irregular at the Phonetic Form (PF) results from the movement and deletion of duplicate syntactic elements. This deletion of the syntactic features is done to satisfy the economic considerations.  It is also reflected that the disjunctive co-ordinands have taxis and logico-semantic type relations or relationships. The paper further divulges that the structure of the disjunctive coordination is the complementiser phrase (CP), and the category label of the disjunctive coordinator/or/ is the complementiser (C). That is, it belongs to the C category.